Paternalizm prawniczy a tożsamość polskiej kultury prawnej - Skuczyński, Paweł (Filozofia Publiczna i Edukacja Demokratyczna, 2013)
The model of legal profession is one of the most important features of every legal culture and constitutional identity. The paper aims at explaining the identity of Polish legal profession according to their history and evolution of Polish political and constitutional basic ideas. The argument is that the strongly manifested element of this identity is lawyers’ paternalism. That means lawyers act to protect the interest of their clients often without an alignment or even against their clients will. This attitude toward the lawyer-client relationship is deeply rooted in Polish legal culture, especially in interconnection of two discourses. First is the egalitarian one which establishes the task of lawyers as to provide to everyone equal legal aid and to protect everyone’s rights and liberties. Second is the elitist one that tend to justify the claim that effective legal aid and the protection of right and liberties is possible only through some special abilities and skills of lawyers which not everyone could possess.